Intellectual Property Rights in Startup Business Models - Strömberg, Fredrik; Jansson, Caspar (My University, 2018)
Problem: Commercialization of an innovation confronts small technology startups with a range of decisions regarding what strategies and business models to opt for. Small startup innovators often struggle to appropriate the value their innovation creates for the market. Instead it is frequently the imitators who capture a larger portion of the value. This thesis aims to investigate the role of IPRs when startups shape their business models, in order to maximize value appropriation Purpose: The purpose of this thesis is to investigate how hardware startups can shape their business models to maximize profits from their innovation. More specifically what role intellectual property rights have in shaping the business model. Method: The thesis is based on a multiple case study with semi-structured interviews. Data was gathered using purposive sampling and was then analyzed with a thematic approach based on the theoretical framework and the contents of the interviews during the second half of the process. Theoretical framework: The theoretical framework first introduces the area of profiting from innovation, including the appropriability regime. This is followed by a section on intellectual property rights, a key factor in the appropriability regime and profiting from innovation. Third, a section on startup strategy is presented, highlighting some key strategic factors for successful value appropriation. Finally, literature on business models is presented, with a focus on the business model canvas. Findings: In the findings, first, the influences from IPRs on various parts of the business model are presented, which shows that IPRs play a key role in shaping the value proposition, key activities, key resources and key partnerships. Second, the influence from other factors of which IPRs are also a part, are presented, indicating a circular relationship between IPRs and the business model. Lastly, the effect of resource constraints on the business model is presented to provide a reference for the other factors. Analysis: In the analysis section, the findings are analyzed through the theoretical framework. The analysis shows that many firms act according to what is suggested by the literature. Customer demand and resource constraints seem to limit the effects of IPRs on the business model. Conclusion: The thesis concludes that IPRs widen the value proposition options by enabling licensing. IPRs allow for more narrow value propositions. They are also used in key activities such as sales and marketing to indicate quality. IPRs enable outsourcing of manufacturing and can play a key role in establishing partnerships.
Keywords: Övrig annan teknik; Innovation och entreprenörskap (nyttiggörande); Other Engineering and Technologies not elsewhere specified; Innovation & Entrepreneurship